Equity / Sarah Worthington. - Worthington, Sarah (Clarendon law series., 2006)
Equity is traditionally regarded as the 'conscience' of the law, though emphasis is usually placed on the law of trusts. This book provides an outline of the basic principles of equity, illustrated by historical and contemporary examples of equity's operation.